Lymph Drainage in Pregnant Women - Sylvia Cataldo Oportus; Lilian de Paiva Rodrigues; José Maria Pereira de Godoy; Maria de Fátima Guerreiro Godoy (Hindawi Limited, 2013)
Aim. The aim of this study was to evaluate the efficacy of lymph drainage to reduce edema of pregnant women. Method. Pregnant women (30 limbs) from the Obstetrics Outpatient Clinic of the Medical School of Santa Casa in São Paulo in the period December 2009 to May 2010 were enrolled in this quantitative, prospective study. The patients, in the 5th to 8th months of gestation, were submitted to one hour of manual lymph drainage of the legs. The volume of the legs was measured by water displacement volumetry before and after one hour of drainage using the Godoy & Godoy manual lymph drainage technique. The paired t-test was used for statistical analysis with an alpha error of 5% being considered significant. Results. Manual lymph drainage significantly reduced swelling of the legs of pregnant women during the day (P=0.04). Conclusion. Manual lymph drainage helps to reduce limb size during the day of pregnant women.